Welfare Gains to Origin Households: Comparing Internal and International Migration of South Indians - Ganesh K. Seshan
A panel data of households from Kerala, India is used to study the welfare gains experienced by origin households whose members migrated overseas and within India between 1998 and 2003. Accounting for endogenous migration choices, the welfare gains to migrant households over this period as reflected in housing investments and durable assets ownership, is found to exceed those of non-migrant families. In addition, the asset gains to sending household whose members migrated overseas are similar to those with interstate migrants. The results are consistent with low ability individuals taking advantage of international wage differentials that generates gains to left-behind household that are at least comparable to gains derived from higher ability individuals pursuing employment opportunities within India.